Spectrum and Prevalence of CALM1-, CALM2-, and CALM3-Encoded Calmodulin Variants in Long QT Syndrome and Functional Characterization of a Novel Long QT Syndrome–Associated Calmodulin Missense Variant, E141G. (April 2016) - Boczek, Nicole J.; Gomez-Hurtado, Nieves; Ye, Dan; Calvert, Melissa L.; Tester, David J.; Kryshtal, Dmytro O.; Hwang, Hyun Seok; Johnson, Christopher N.; Chazin, Walter J.; Loporcaro, Christina G.; Shah, Maully; Papez, Andrew L.; et al.
Abstract : Background—: Calmodulin (CaM) is encoded by 3 genes, CALM1, CALM2, and CALM3, all of which harbor pathogenic variants linked to long QT syndrome (LQTS) with early and severe expressivity. These LQTS-causative variants reduce CaM affinity to Ca 2+ and alter the properties of the cardiac L-type calcium channel (CaV 1.2). CaM also modulates NaV 1.5 and the ryanodine receptor, RyR2. All these interactions may play a role in disease pathogenesis. Here, we determine the spectrum and prevalence of pathogenic CaM variants in a cohort of genetically elusive LQTS, and functionally characterize the novel variants. Methods and Results—: Thirty-eight genetically elusive LQTS cases underwent whole-exome sequencing to identify CaM variants. Nonsynonymous CaM variants were over-represented significantly in this heretofore LQTS cohort (13.2%) compared with exome aggregation consortium (0.04%; P <0.0001). When the clinical sequelae of these 5 CaM-positive cases were compared with the 33 CaM-negative cases, CaM-positive cases had a more severe phenotype with an average age of onset of 10 months, an average corrected QT interval of 676 ms, and a high prevalence of cardiac arrest. Functional characterization of 1 novel variant, E141G-CaM, revealed an 11-fold reduction in Ca 2+ -binding affinity and a functionally dominant loss of inactivation in CaV 1.2, mild accentuation in NaV 1.5 late current, but no effect on intracellular RyR2-mediated calcium release. Conclusions—: Overall, 13% of our genetically elusive LQTS cohort harbored nonsynonymous variants in CaM. Genetic testing of CALM1-3 should be pursued for individuals with LQTS, especially those with early childhood cardiac arrest, extreme QT prolongation, and a negative family history. Abstract : Supplemental Digital Content is available in the text.